Development of Teaching Materials to Support Merdeka Curriculum Learning on Basic Law of Chemistry Phase E - Fallahu Fauzan; Mawardi Mawardi; Okta Suryani (IKIP Mataram, 2023)
This research aims to develop teaching materials to support merdeka curriculum learning on the basic laws of chemistry phase E SMA / MA. This research uses the Educational Design Research (EDR) method using the Plomp development model as its research approach. The subjects of this study were three chemistry lecturers, two chemistry teachers and nine students with high, medium and low ability levels. Data were collected through the use of validation questionnaires and practicality questionnaires. The results showed that the teaching materials developed had an average validity of 0.89 which was included in the valid category. Furthermore, the results of the practicality test showed that students rated the teaching materials with an average practicality of 93%, which is classified as very practical. Similarly, teachers assessed the teaching materials with an average practicality of 95%, also considered very practical. Overall, the results of the study indicate that the development of teaching materials to support merdeka curriculum learning on basic chemical laws is valid and practical.